Author Correction: A changeable day in the life of Venus. Issue 12 (December 2018) - Keane, James
In the version of this Sketch-Up originally published, labels describing atmospheric torques acting on Venus were incorrect. The sketch suggested that the speed-up effect of mountain waves is balanced by a slow-down from thermal tides; instead, both mountain waves and thermal tides speed up the rotation, and this effect is balanced by a slow-down from the solar gravitational torque on the solid body, which is transmitted to the atmosphere. This error has now been corrected in the online versions by adjusting the relevant labels; that is, "Mountain waves speed the planet up" has been changed to "Mountain waves and thermal tides speed the planet up", and "Thermal tide slows the planet down" has been changed to "Solar gravitational torques slow the planet down".